2016
DOI: 10.1016/j.ijcard.2016.06.249
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative atrial fibrillation is associated with a pre-existing structural and electrical substrate in human right atrial myocardium

Abstract: BackgroundPost-operative atrial fibrillation (POAF) is a major health economic burden. However, the precise mechanisms in POAF remain unclear. In other forms of AF, sites of high dominant frequency (DF) in sinus rhythm (SR) may harbour ‘AF nests’. We studied AF inducibility in relation to substrate changes using epicardial electrograms and cardiomyocyte calcium handling in the atria of AF naïve patients.MethodBipolar electrograms were recorded from the lateral right atrial (RA) wall in 34 patients undergoing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…Factors promoting development of EPoAF following cardiothoracic surgery include, for example, inflammatory response, sympathetic activation, and oxidative stress. In addition, EPoAF is not solely initiated by the presence of these triggers, but also depends on the presence and extensiveness of an arrhythmogenic substrate . Atrial alterations on structural, electrical, and contractile levels cause a higher vulnerability for development of AF .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors promoting development of EPoAF following cardiothoracic surgery include, for example, inflammatory response, sympathetic activation, and oxidative stress. In addition, EPoAF is not solely initiated by the presence of these triggers, but also depends on the presence and extensiveness of an arrhythmogenic substrate . Atrial alterations on structural, electrical, and contractile levels cause a higher vulnerability for development of AF .…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows additional clinical characteristics of patients with and without LPoAF. Overall time to LPoAF diagnosis was 6 (3-6) months and was similar in patients with (N=40, 6 [3][4][5][6]) and patients without (N=4, 8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]) preoperative AF (P=0.708).…”
Section: Late Postoperative Afmentioning
confidence: 91%
See 1 more Smart Citation
“…This may reflect extra-PV mechanisms for post-operative AF, as supported by a recent randomized trial by Skanes et al, which showed no benefit of intraoperative PVI on development of postoperative AF following coronary artery bypass graft surgery [12]. These findings suggest a role for non-PV triggers or atrial ‘substrate’, i.e., mechanisms that sustain AF after it has been triggered, in post-operative AF, recently shown in the right atrium of patients undergoing elective CABG [13]. …”
mentioning
confidence: 84%
“…Millipore-Sigma reports that ABT13 reacts with rabbit, mouse, and human SLN on immunoblot at 1.5 µg/mL pAb, as corroborated for rabbit SLN using 0.5 µg/mL pAb ABT13 (1:1000 dilution) and fluorescent secondary antibody detection (Figure S8). pAb ABT13 has been validated for SLN immunoblotting using human right atrium homogenate (189) and mouse soleus and diaphragm homogenates (190). Here pAb ABT13 was used for primary labeling at 1:1000 dilution, with positive detection of SLN in rabbit SR (Figure S7), plus synthetic rabbit and human SLN.…”
Section: Commercial Anti-sln Polyclonal Antibodiesmentioning
confidence: 99%